Ethnobotanical survey on medicinal plants in the Djurdjura National Park and its influence area, Algeria - Meddour, Rachid; Sahar, Ouahiba; Ouyessad, Malika (Ethnobotany Research and Applications, 2020)
Background: It is recognized that 80% of the world population uses traditional medicine for primary health care. In the Maghreb, there is a traditional health system where active medicinal plants are ever-present. The main objective of this ethnobotanical survey, conducted through a protected area, the National Park of Djurdjura, is to assess ethnobotanical knowledge, focusing on traditional uses of medicinal plants, and to provide a comprehensive inventory of plants used even today by people of this rural area. This knowledge, traditions and ancestral skills are transmitted mainly orally. It is therefore essential to collect ethnomedicinal information especially in a conservative perspective and recovery of ancestral knowledge on traditional herbal medicine. Methods: This study was performed in the National Park of Djurdjura (province of Tizi Ouzou), at three villages located in the park or in the immediate vicinity: Ait Ouabane, Ait Allaoua and Darna. This National Park was labelled as a Biosphere Reserve in 1997. The ethnobotanical survey fieldwork was conducted with 31 informants belonging to the local inhabitants, who are native of villages surveyed, through direct interviews with a pre-established questionnaire, largely inspired from previous questionnaires developed in the Maghreb. The sample selection was subjective and directed, in the sense that, in general, we obtained information from key informants considered as local experts of medicinal flora in each village concerned by the survey. The ethnobotanical information obtained was entered in a table of raw and processed data using the Microsoft Excel® spreadsheet to control and standardize information on several aspects. Results: Overall, 80 plants with medicinal interest, have been identified; they belong to 43 families and 73 genera. The Lamiaceae family is the most represented with 12 different species. Utmost medicinal plants (88.75%) are non-toxic. Furthermore, they are often multipurpose plants, since their medicinal, food and fodder utilities. Particularly, 41 of these wild plants yet still have an interest in food for rural populations. The toxicity of some herbs (10.38%) is well known. They are used with caution in traditional medicine, and only for external use. This plant toxicity concerned humans and animals. The large majority of plants inventoried (80.2%) is spontaneous and occurs in natural habitats. The plants used in traditional medicine grow in forests (20.7% of the plants surveyed) and in maquis and garrigue (17.9%). Anthropogenic habitats, and fallow fields (17.9%) and cultures (19.8%) support a high proportion of medicinal plants. Plants of wetlands are involved at a high rate (13.21%) in the traditional pharmacopoeia in National Park of Djurdjura. The 80 medicinal plant species recognized are used in the preparation of 239 therapeutic recipes, which can treat 70 diseases and ailments in total. Nine traditional recipes are prepared with Olea europaea subsp. europaea. Eight recipes are prepared with Origanum glandulosum and either "Quedhran” tar of Cedrus atlantica, montane species widespread in our study area. Six recipes are prepared with Juglans regia and five recipes with each of the following plants: Pistacia lentiscus, Nerium oleander, Silybum marianum and Thymus numidicus. Finally, the majority of plants (72) are used in 1-4 recipes of traditional medicine. The 70 listed diseases are gathered into 10 major disease groups: 4 groups contain between 10 and 14 diseases (digestive disorders, blood circulation, skin and respiratory). The range of plants used (47) in the group of digestive disorders, is higher than that of the other diseases groups. This group of digestive problems is easier to deal with because of the wider range of medicinal plants used as remedies. The part of the plant most used is the aerial part with 81.48%, because of its availability. Infusion of fresh leaves is the most common preparation (24.26%). Conclusion: This ethnobotanical survey among rural and traditional healers allowed us to transcribe faithfully oral knowledge, exposed today to a major risk of loss. Holders of this ethnomedicinal knowledge are 50 years old and over (often-illiterate women). The use of plants for therapeutic purposes is legitimate, if it does not constitute a threat to biodiversity. The preservation of this floristic diversity and especially rare species is necessary for the sustainability of this traditional medicine in Djurdjura National Park. Ethnobotanical data acquired on reveal important medicinal knowledge (great number of plants, diversity of uses and practices). Which suggests promising perspectives in research and clinical pharmacology. It is understood that a significant proportion of the financial benefits of such an approach must return to holders of this knowledge in fairness in a global socio-economic part of sustainability. Keywords: Traditional knowledge, ethnomedicinal study, rural population, protected area, Kabylia.